Handgrip Strength Cut-Off Points for Early Detection of Cardiometabolic Risk in Chilean Children - Garcia-Hermoso, A (Springer Science and Business Media Deutschland GmbH, 2021)
The aim of this study was to determine whether handgrip strength is associated with cardiometabolic risk in children. The secondary aim was to establish sex-specific handgrip strength cut-off points for early detection of cardiometabolic risk. A total sample of 452 Chilean children (267 girls and 185 boys) aged 7–9 years old was analyzed. Muscle fitness was measured by an adjustable dynamometer and normalized by body mass (i.e., handgrip strength/body mass). Sex-specific cardiometabolic risk scores were computed as the sum of the waist-to-height ratio (Equation 1) or waist circumference (Equation 2) and insulin, triglycerides, high-density lipoproteins, and glycemia levels. Receiver operating curve (ROC) analyses were performed to identify those with cardiometabolic risk scores > 1 standard deviation above the mean. ROC analyses showed a significant discriminating accuracy of normalized handgrip strength in identifying cardiometabolic risk in boys (≤ 0.33) and girls (≤ 0.40) using both equations. The highest sensitivity was offered by Equation 2 for boys [46%; 95% CI (32–59%)] and for girls [71%; 95% CI (60–80)]. The greatest specificity was also offered by Equation 2 for boys [82%; 95% CI (74–88)] and girls [63%; 95% CI (55–70)]. Since the values obtained by ROC analyses are low (especially in boys), caution is warranted regarding the strength of the existing evidence base. Conclusion: These specific cut-off points according to sex for possible cardiometabolic risk could be used by Chilean health professionals and school staff as an initial assessment in the field setting.What is known • There is strong evidence for the importance of muscular fitness during childhood and adolescence for cardiometabolic risk. • There has been no research to establish minimum handgrip strength capacity levels to predict cardiometabolic risk among Chilean children.What is new • Cut-off points for handgrip strength relative to body mass to identify cardiometabolic risk in Chilean children are 0.33 in boys and 0.40 in girls.• The early use of these cut-off points and its appropriate identification could have benefits of preventive and diagnostic therapeutic intervention and as a starting point to define adequate levels of handgrip strength. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.